2020
DOI: 10.3390/ijerph17176219
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Resilience, Everyday Stress, Self-Efficacy, Self-Esteem, Emotional Intelligence, and Empathy on Attitudes toward Sexual and Gender Diversity Rights

Abstract: The present study forms part of the project “Cross-disciplinary education for sexual, body, and gender diversity” (Code 419). The aim of this study was to analyze the role played by the psychoeducational variables involved in burnout (resilience, self-efficacy, self-esteem, emotional intelligence, empathy, and everyday stress) on attitudes toward sexual and gender diversity rights. Participants comprised 170 university students undertaking a degree in primary education. Instruments were administered to assess … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 54 publications
0
5
0
1
Order By: Relevance
“…Momentary mood is expected to affect QoL both directly and indirectly, mediated by psychological resilience ( 61 ). Finally, in line with the predicted effects of gender on QoL ( 56 ), we hypothesized that gender will directly contribute to QoL. Additionally, following the ongoing debate regarding the impact of gender on mental health status and on psychological resilience, we hypothesized an additional direct contribution of gender to both variables ( 37 ).…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…Momentary mood is expected to affect QoL both directly and indirectly, mediated by psychological resilience ( 61 ). Finally, in line with the predicted effects of gender on QoL ( 56 ), we hypothesized that gender will directly contribute to QoL. Additionally, following the ongoing debate regarding the impact of gender on mental health status and on psychological resilience, we hypothesized an additional direct contribution of gender to both variables ( 37 ).…”
Section: Introductionmentioning
confidence: 88%
“…Therefore, in our model, we refer to self-efficacy as part of the global concept of psychological resilience. In addition, there may be gender differences related to the two constructs: while female adolescents were found to report lower self-efficacy under stress compared to their male counterparts ( 55 , 56 ), others report higher levels of challenges among newly-recruited females soldiers ( 24 ).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, Morales et al [29] cited some characteristics of individual resilience, such as self-esteem, independence or relational capacity, all mentioned by the women in our study as personal coping tools. We confirmed that the women in our research showed that they were able to move on.…”
Section: Discussionmentioning
confidence: 52%
“…Regarding the objective related to the analysis of the relationship between attitudes towards gender equality with other psychoeducational variables, such as thinking styles, further research is needed. A previous study [44] demonstrated the existence of correlations between the variables' attitudes towards gender equality and those of resilience and burnout. Comparably, a second study [45] indicated that women tend to be more empathetic than men, and that less empathetic people are more likely to experience behavior that is more violent, such as bullying in the school environment.…”
Section: Discussionmentioning
confidence: 90%